Analisis Aplikasi Ujian Online Bee Smart Pada SMK Negeri 4 Palembang Menggunakan Metode Technology Acceptance Model - Saputri, Okta; Hartati, Eka; Yunifa, Wiza (Universitas Multi Data Palembang, 2024)
SMK Negeri 4 Palembang has an online exam application called Bee Smart. Bee Smart is an application used to make it easier for students to take Mid-Semester Exams and Final Semester Exams. This research aims to find out what factors influence the acceptance of the Bee Smart online exam application at SMK Negeri 4 Palembang using the Technology Acceptance Model (TAM) method. Based on the results of the correlation test, it shows that the variables are interconnected with the highest value of 0.896. Based on the f test and t test, the results show that there is a simultaneous and partial influence because the significance value is 0.000 < 0.05. This shows that all hypotheses are accepted, meaning that users of the Bee Smart online exam application accept the Bee Smart application at SMK Negeri 4 Palembang as a means to simplify the school exam process.